An Analysis of Main Character’s Personality in Kitchen Novel by Banana Yoshimoto - Putri Amifalahiya Iqlima; Risa Triassanti (Pro-ELLitera, 2023)
Novel is a form of literary work that is presented realistically and complexly. In a novel, there are two constituent elements, namely extrinsic and intrinsic elements. Extrinsic elements in the novel are support that indirectly affects the content of the novel. Meanwhile, the intrinsic elements contained in a novel include themes, characters and characterizations, plot, setting, point of view, moral value, language style. The purpose of this study is to analyze main character’s personality in Kitchen novel by Banana Yoshimoto. This research used qualitative descriptive methods to gain a deep understanding of main character’s personality in Kitchen novel by Banana Yoshimoto. The data were analyzed using personality theory stated by Sigmun Freud. From the results of data analysis, the researcher found three major system with three Id, two ego, and two superego contained in the main character’s personality.